PERBEDAAN HASIL BELAJAR EKONOMI SISWA YANG MENGGUNAKAN MODEL PEMBELAJARANKOOPERATIFTIPETHINK PAIR SHARE (TPS) DENGAN TIPE STUDENT TEAMS ACHIEVEMENT DIVISION(STAD)SISWA KELAS XI IPS SMAN 11 PADANG - Sofianti, Dina; Akhirmen, Akhirmen; Areva, Desi (Pendidikan Ekonomi, 2013)
ABSTRACT This research is aimed at analyzing the difference of learning points by using the cooperative learning models between Think Pair Share (TPS) and Student Teams Achievement Division (STAD) types of the XI-grade students of IPS SMAN 11 Padang. It is an experimental research. The population of this research is all XI-grade students of IPS SMAN 11 Padang, who were registered in the year 2013-2014. Two samples were selected by using the technique of Puposive Sampling method. The data of this research is primary data, and the data analyses are descriptive and inductive, conducted through t-test by first making tests of normality and homogeneity of both sample variants. Based on the data analyses, it is obtained that the learning points for the experimental class 1 is 76.80 and the experimental class 2 is 65.64 on the average, meaning that Sig 0.018 is smaller than α = 0.05. From the hypothesis tests, tcalc.is 2.444 and ttable is 1.67, so that H0 is rejected, meaning that there is the difference between Think Pair Share (TPS) and Student Teams Achievement Division (STAD).From the results of research it is hoped that this could provide a solution for the problem of lowering learning points especially in economics subject. Finally, for improving the learning points of economical students, it is suggested for teachers to consider the learning models from Think Pair Share (TPS) and Student Teams Achievement Division (STAD). Keywords: Think Pair Share (TPS), Student Teams Achievement Division (STAD), Economical Learning Points